Spatial and temporal variability in reference evapotranspiration in Oklahoma - Itenfisu, Daniel, author; Elliott, Ronald L., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
Evapotranspiration from a satellite-based s Reference evapotranspiration (ETref) is an important indicator of a region's climate, specifically its evaporative demand. Evapotranspiration (ET) is a key component of the energy and water balance of a given environment. Information on ETref is essential in the quantification of water use in agricultural, natural and urban landscape systems. Various formulations of ETref have been used over the past several decades. Recently, the Task Committee of American Society of Civil Engineers (ASCE) Evapotranspiration in Irrigation and Hydrology Committee developed a standardized procedure for computing reference evapotranspiration for grass (ETos) and alfalfa reference crops. Accurate ETref computations using data from a network of weather stations require a careful check of the data quality and the similarity of site surface conditions to reference standards when data is acquired. Despite a lack of coastal effects or significant orographic influences, Oklahoma appears to exhibit considerable spatial and temporal variability in evaporative demand. The availability of the Oklahoma Mesonet, a comprehensive automated weather station network, provides an opportunity to study ETref patterns across the state and through time. The Mesonet is a network of 115 well-distributed and well-maintained stations. Using seven years of quality assured data from this network, daily ETos, has been calculated for 40 sites representing the diverse Oklahoma climate. Spatial and temporal variability in ETos is discussed. This analysis is a precursor to on-line mapping of reference evapotranspiration and identification of geo-spatial ETos zones.
USCID/EWRI conference
Reference evapotranspiration in Oklahoma
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.